(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The article analyzes issues related to national values and the evolution of the formation of a national character. Upbringing is the most important component of a national character, the socialization of a person, the role of national values in this process is studied based on the results of sociological research. Also, in building a social state in New Uzbekistan, opinions are expressed on the enrichment of national values and national character with new content. At the present stage of development, information is given on the phenomena of sociability in a person, spiritual maturity, moral purity, living by the command of conscience, leaning on national values and a strictly national character.